SYSTEM OF METHODS FOR FORMING PROFESSIONAL WORLD VIEW IN PUPILS BASED ON CHEMICAL KNOWLEDGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the importance of the formation of the professional worldview of students, as well as the role and influence of chemical knowledge in the formation of the professional worldview of students, the achievement of a broad professional worldview based on chemical knowledge.The socio-economic changes taking place in our country have led to the search for the formation of the professional worldview of students. The vacant “ideological space” of the recent past was not completely filled with positive content, which negatively affected the formation of students' identity in schools.In modern conditions of civilizational development, the formation of the professional worldview of students occupies one of the leading places. Worldview - ensures the development of an integral personality, capable of consciously and critically interacting with the outside world. Many domestic and foreign scientists consider it expedient to accumulate static knowledge in the process of intellectual development of a student in the educational process, the formation of dynamically structured systems of mental actions, differentiated and individualized programs.